THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND THE DEGREE OF HYPERTENSION AT PUSKESMAS PANJANG KOTA BANDAR LAMPUNG - Sellyana Hani; Alfianto Martin (Sean Institute, 2023)
In 2010, the World Health Organization identified hypertension as a significant risk factor for disease worldwide and nearly half of all adults have hypertension. In 2016, hypertension was ranked in the top 10 disorders in Lampung Province, especially in Bandar Lampung. Hypertension has many risk factors, one of which is physical activity. Therefore, this study aims to examine the relationship between hypertension and physical activity at the Panjang Health Center in Bandar Lampung City. This study uses a cross-sectional analytic observational methodology. This study used the General Physical Activity Questionnaire (GPAQ) and medical records for data collection—70 people filled out the questionnaire between December 2021 and April 2022. The results showed that 50 people (75.7%) had grade 1 hypertension, 11 (16.6%) had grade 2 hypertension, and 5 people (15.6%) suffered from grade 3 hypertension. Among the patients with hypertension, 18 people had light physical activity (27.2%). A total of 24 respondents who suffer from hypertension (36.4%) have moderate physical activity. A total of 24 respondents with hypertension (36.4%) were physically active in the heavy category. The Chi-Square statistical test found no significant relationship between the degree of physical activity and hypertension at the Panjang Health Center in Bandar Lampung City (p = 0.261).